2004
DOI: 10.1097/01.olq.0000118081.54177.95
|View full text |Cite
|
Sign up to set email alerts
|

New Estimates of Herpes Simplex Virus Type 2 Seroprevalence in England

Abstract: After adjustment for age, sex, and geographic location, there was no evidence of a change in seroprevalence between 1991 and 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Overall, HSV-2 seropositivity in Greece of 10% is comparable with results from other European countries such as Belgium (11%), 12 England (10%), 13 Germany (14%), 12 Finland (13%), 12 Israel (9%), 14 the Netherlands (9%) 12 and Poland (9%). 15 HSV-2 seroprevalence in Greece was higher than that reported in Italy (6%) 16 and Spain (4%), 17 and lower than that in France (17%), 18 Switzerland (19%) 19 and Bulgaria (24%).…”
Section: Discussionsupporting
confidence: 66%
“…Overall, HSV-2 seropositivity in Greece of 10% is comparable with results from other European countries such as Belgium (11%), 12 England (10%), 13 Germany (14%), 12 Finland (13%), 12 Israel (9%), 14 the Netherlands (9%) 12 and Poland (9%). 15 HSV-2 seroprevalence in Greece was higher than that reported in Italy (6%) 16 and Spain (4%), 17 and lower than that in France (17%), 18 Switzerland (19%) 19 and Bulgaria (24%).…”
Section: Discussionsupporting
confidence: 66%
“…HSV-2 seroprevalence in this Polish population (median age of 34) (9.1%) is comparable to similarly aged women from population based surveys in Barcelona, Spain (11%) 15 and England (12.3%), 16 and slightly higher than in population based samples from Spain (2.7-,5%), 17 18 Czech Republic (6%), 19 and Central Italy (4.8%). 20 HSV-2 seropositivity overall in Poland was lower, however, than in women from northern and eastern Europe, 10 19 such as a population based sample in Germany (14%); 19 two studies of women in Norway(25-28%) 21 22 ; Swedish studies of pregnant women (,34%) 23 24 ; and population based studies 19 in Finland (13%), the Netherlands (9%), Bulgaria (24%), and Belgium (11%).…”
Section: Discussionsupporting
confidence: 56%
“…Age standardised HSV-1 and HSV-2 seroprevalence were 90.4% and 9.3%, respectively, in 2257 samples from serum banks. Age standardised HSV-2 seropositivity was higher in women (9.7%) than men (8.8%), and increased notably with age from 4% in [15][16][17][18][19] year olds to 12% in those 40 years or older. HSV-1 seropositivity was higher than HSV-2 in each age group surveyed and was not associated with HSV-2 serostatus.…”
Section: Discussionmentioning
confidence: 89%
“…After adjustment for age, sex, and geographic location, there was no evidence of a change in seroprevalence during the study period. 7 The declining trends of the HSV-2 seroprevalence and transmission rate cannot be explained as an artifact as a result of inaccuracy of the laboratory assay (i.e., false-negative and false-positive results). We used an ELISA kit of high sensitivity and specificity 10 ; all assays were performed in the same laboratory, under similar conditions by the same laboratory technicians who were unaware of each subject's personal characteristics and other tests results.…”
Section: Discussionmentioning
confidence: 98%
“…6 Similarly, a recently published study of HSV-2 seroprevalence in England between 1991 and 2000 in a large study group aged 16 to 64 years revealed that there was no evidence of a change in seroprevalence during the study period. 7 In contrast, there has been a documented decline in the rate of HSV-1 infection in adolescence in some developed countries, which may be the result of improved standards of living. 8 Consequently, an increasing proportion of adolescents may be HSV-1-naive at sexual debut, and together with changes in sexual behavior (increased rates of oral-genital contact), there have been increases in the proportion of genital HSV infection attributable to HSV-1.…”
mentioning
confidence: 91%